The application of custom 3D-printed prostheses with ultra-short stems in the reconstruction of bone defects: a single center analysis - Zhang, Peng; Tian, Wen; Li, Po; Zhang, Fan; Qu, Guoxin; Du, Xinhui; Liu, Guancong; Niu, Xiaoying (Frontiers in Bioengineering and Biotechnology, 2024)
Objective: Considering the advantages and widespread presence of 3Dreprinting technology in surgical treatments, 3D-reprinting porous structure prostheses have been applied into wide range of the treatments of bone tumor. In this research, we aimed to assess the application values of the 3D-reprinting custom prostheses with ultra-short stem for restoring bone defect and maintaining arthrosis in malignant bone tumors of lower extremities in children.Methods: Seven cases of pediatric patients were included in this study. In all cases, the prostheses were porous in titanium alloy with ultra-short stem.MSTS 93 (Musculoskeletal Tumor Society) score was recorded for the functional recovery of the limbs. VAS (Visual Analogue Scale) score was utilized to assess the painful degree of the patients. X-ray and MRI (Magnetic Resonance Imaging) were applied to evaluate the bone integration, prostheses aseptic loosening, prostheses fracture, wound healing and tumor recurrence during following up.Results: During following up, neither patients developed any postoperative complications, including prostheses aseptic loosening, prostheses fracture and tumor recurrence. Radiological examinations during the follow-up showed that prostheses implanted into the residual bone were stably fitted and bone defects were effectively reconstructed. The MSTS 93 scores were 24.9±2.9 (20-28). VAS scores were decreased to 5.8±1.2 (4.0-7.0). No statistically significant differences in leg length discrepancy were observed at the last time of follow-up.The 3D-reprinting technology can be effectively applied throughout the entire surgical treatment procedures of malignant bone tumors, offering stable foundations for the initial stability of 3D-reprinted prostheses with ultra-short stems through preoperative design, intraoperative precision operation, and personalized prosthesis matching.With meticulous postoperative follow-up, close monitoring of postoperative complications was ensured. These favorable outcomes indicate that the utilization of 3D-reprinted custom prostheses with ultra-short stems is a viable alternative for reconstructing bone defects. However, further investigation is warranted to determine the long-term effectiveness of the 3D-reprinting technique.